Development of GNSS measurement models with the use of base stations and radio modules - Celms, A.; Trevoho, I.; Kolodiy, P.; Ratkevics, A.; Lidumnieks, T.; Brinkmanis-Brimanis, M. (Видавництво Львівської політехніки, 2024)
Global navigation satellite systems (GNSS) historically been known as one of the newest technologies since the 1970s. GNSS originally developed for military purposes in the USA (GPS – Global Position System). There are several satellite systems in the world. Satelites, International Research Base Stations, regional/national and local base stations form a permanent geodetic frame. Research on the size and shape of the Earth-planet, climate, sea, urban planning. In geodesy, a network of global positioning base stations makes it possible to asses the movements of continents, land plates at international level. GNSS is an important technology in navigation, logistics, economics, land surveying and other “geo” sectors. GNSS equipment/receivers and their manufacturers are applying new designs and electronics. Initially GNSS instruments used with single frequency signal reception, later expanding the number of GNSS signal channels to two frequencies. Such technological improvements nowadays improve the certainty, reliability and accuracy – the overall quality – of GNSS measurements. The GNSS base station enables the surveyors, other user’s GNSS receiver to determine coordinates with an accuracy of two centimeters in real time (RTK) and with an accuracy of five millimetres using the accumulated post-processing data. Various types of factors hamper GNSS measurements. The GNSS signal (radio wave) travels in airspace, in urban environments and is a physical parameter. Any obstacle – tree, building walls, and atmospheric effect – makes GNSS measurements less accurate. The GNSS signal must be strong and free from attenuation and suppression effects. This study develops GNSS models that show the comparison, certainty and reliability of GNSS measurements using different types of GNSS techniques. Evaluation of Latvian Global Positioning Reference Station Network – LatPos system measurements against a corresponding RTK solution method using Latvian Global Positioning Network geodetic point (G2 class). point (G2 class).
Keywords: GNSS; Global position measurements; Real Time Kinematic (RTK); LatPos; 528; 629.056